Genetic variability of inflammatory genes in the brazilian population - Santos, Marcelo (2013)
Inflammatory gene variants have been associated with several diseases, including cancer, diabetes, vascular diseases, neurodegenerative diseases, arthritis, and others. Therefore, determining the population genetic composition of inflammation-related genes can be useful for the determination of general risk, prognostic and therapeutic strategies to prevent or cure specific diseases. We have aimed to identify polymorphism genotype frequencies in genes related to the inflammatory response in the Brazilian population, namely, IjBL - 62AT, IjBL - 262CT, tumor necrosis factors alpha (TNFa) - 238GA, TNFa - 308GA, lymphotoxin-alpha (LTa) + 80AC, LTa + 252AG, FAS - 670AG, and FASL - 844TC, considering the white, black, and Pardo ethnicities of the Sa˜o Paulo State. Our results suggest that the Brazilian population is under a miscegenation process at the current time, since some genotypes are not in the Hardy–Weinberg equilibrium. In addition, we conclude that the Pardo ethnicity is derived from a complex mixture of ethnicities, including the native Indian population.